Surat Keterangan Kepala Desa sebagai Bukti yang Menguatkan Kepemilikan Tanah - Saniathira Alma Haryanto (Jurnal Hukum Lex Generalis, 2024)
SKT (Letter of Village Head) is an essential document supporting the land registration process, particularly in areas without formal land certificates. SKT is often used as initial evidence of land possession before proceeding with the registration process at the National Land Agency (BPN). This study examines case studies such as Decision Court No. 9/PDT.G/2010/PN.SML from the Saumlaki District Court and Decision Court No. 5/Pdt.G/2023/PN.MDL from the Mandailing Natal District Court. The findings show that SKT issued by the village head holds legal validity to strengthen claims of land ownership, provided it is issued following proper procedures and within the legal authority's scope. However, SKT cannot serve as definitive proof of ownership without being followed by a formal land registration process.